The Life Cycle of the Common Octopus - Knight, Emma (Emma L.) ([Toronto, Ontario] : Pamela Dorman Books/Viking, 2025)
"A witty, warm and brilliantly told debut that is at once a love story, a story of female friendship and motherhood, and an irresistible mystery surrounding an extraordinary British family. Arriving at the University of Edinburgh for her first term, Pen knows her divorced parents back in Canada are hiding something from her. She believes she'll find the answer here in Scotland, where an old friend of her father's--now a famous writer known as Lord Lennox--lives. When she is invited to spend the weekend at Lord Lennox's centuries-old estate with his enveloping, intriguing family, Pen begins to unravel her parents' secret and to fall in love for the first time... Her best friend, Alice, an aspiring actor, is starring in a university production and making the most of the feminine power she wields--until a tryst with her tutor threatens to spin out of control. As Pen experiences the sharp shock of adulthood, she uncovers the truth about her own family and comes to rely on herself for the first time in her life. A rich and rewarding novel of campus life, of sexual awakening, and ultimately, of the many ways women can become mothers in this world, The Life Cycle of the Common Octopus asks to what extent we need to look back in order to move forward"--.
Read with Jenna title
new book 2025 winter.
Issued also in electronic print.
Keywords: University of Edinburgh -- Fiction; College students -- Fiction; Secrecy -- Fiction; Friendship -- Fiction; Families -- Fiction; Family secrets -- Fiction; Edinburgh (Scotland) -- Fiction